The philosopher's toothache : embodied stoicism in Early Modern English drama - Sherman, Donovan (Rethinking the Early Modern., 2022)
"Informed by work in both classical philosophy and performance studies, this book argues that Stoicism infused the theatrical culture of early modern England. Plays written during this period instruct audiences to cultivate their virtue, self-awareness, and creativity in keeping with Stoic practice"--